Factors that influence person organization fit: case study on UMW Oil & Gas employees / Suhaila Mohd Harun - Mohd Harun, Suhaila (2015)
The present research was conducted at UMW Oil & Gas, Plaza Sentral, Kuala Lumpur. This research is to study and identify the factors that influence Person Organization Fit in the organization. The variables of this study enables the management to identify whether the individuals have a values that congruence to the organization. A great organization will produce efficient employees that help to generate a good output. The qualitative and quantitative data taken from 103 out of 142 respondents that was analyzed to interpret the relationship. The data originally consist of 5 dimension data analysis which includes descriptive analysis, frequencies analysis and multiple regression analysis. It was found that Job Satisfaction, Organizational Commitment, and Job Performance were contributed significantly to Person Organization Fit.